Papel do receptor do fator de agregação plaquetária na resposta inflamatória induzida em modelo experimental de colite ulcerativa - Renata Lacerda de Lima (2016)
Inflammatory bowel diseases (IBD) are inflammatory diseases that affect the gastrointestinal tract and have increased in prevalence all around the world. Ulcerativis colitis and Crohn’s disease are the major chronic IBD and patients show flares of remission and relapses, resulting from an immune response to changes in intestinal microbiota in individuals with genetic predisposition to IBD. Ulcerative colitis affects the colon leading to clinical symptoms such as weight loss, bloody diarrhea, fever and shortening of the colon. PAF is a phospholipid mediator with important pro-inflammatory activity that acts through binding and activation of its receptor, PAFR. PAF have been involved in the induction and severity of IBD, however, the mechanisms of induction of the inflammatory response via PAF in these diseases are not well understood. Therefore, the aim of this study was to investigate the role of PAFR in the inflammatory response during experimental DSS-induced colitis. Our results have demonstrated that animals with genetic deletion of the PAFR have shown exacerbated development of colitis when these were compared to wild type animals. In experimental protocols of acuteor chronic disease and colitis recovery, PAFR - / - animals have presented exacerbated clinical signs of colitis, greater weight loss, changes in stool consistency and severe blending and greater tissue injury. The PAFR - / - animals have shown an exaggerated inflammatory response to induction of ulcerative colitis DSS, mainly characterized by increased MPO activity and IL-1 β production. These animals also exhibited a deficit in the disease recovery after DSS removal. Treatment with a PAFR antagonist, haven’t shown the same effects over disease as the ones found in gene-deficiente mice. Therefore, we suggest that genetic deletion of PAFR interfere in order to delay the inflammation resolution phase and, consequently, the epithelial intestinal regeneration during ulcerative colitis.